Education Policy in Portugal - Sousa, Jesus Maria (Education Policy Analysis Archives, 2000)
The Revolution of 25 April 1974 in Portugal put an end to a forty-eight year old dictatorship, opening the country to democracy. The purpose of this article is to describe education reform from the standpoint of a country that experienced a major political transition and had to start from the very beginning to devise an education policy. Rather than merely describing the organization of the Portuguese education system, I present a condensed analysis of Portuguese education policy, as I view it, making use of indicators of the nature of an education system proposed by D'Hainaut (1980).